2004
DOI: 10.1103/physrevb.70.064105
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and strontium codoping ofLa2NiO4: Room-temperature phase diagrams

Abstract: We present a detailed room temperature x-ray powder diffraction study on La2−xSrxNiO 4+δ with 0 ≤ x ≤ 0.12 and 0 ≤ δ ≤ 0.13. For x = 0.02, 0.04 and 0.06 the oxygen content phase diagrams of the Sr-doped samples show a similar sequence of pure phases and miscibility gaps as for pure La2NiO 4+δ . We find a weak Sr doping dependence of the δ range for the pure LTO, LTT and HTT phases; but overall, the δ ranges of the different phases do not vary strongly for x ≤ 0.06. Drastic changes are observed for x = 0.08 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…Among the TMOs, the La 2-x Sr x NiO 4 , popularly called nickelates, construct good example of such systems with complex interplay between spin-charge-lattice degrees of freedom [5][6][7][8][9][10][11][12][13][14][15][16] . The nickelates have been studied intensively, however, a substantial amount of work is dedicated to the La 5/3 Sr 1/3 NiO 4 , merely due to the fact that the system appears with robust charge stripe ordering for this doping, making it a suitable system to address various functions of the TMO perovskites.…”
Section: Iintroductionmentioning
confidence: 99%
“…Among the TMOs, the La 2-x Sr x NiO 4 , popularly called nickelates, construct good example of such systems with complex interplay between spin-charge-lattice degrees of freedom [5][6][7][8][9][10][11][12][13][14][15][16] . The nickelates have been studied intensively, however, a substantial amount of work is dedicated to the La 5/3 Sr 1/3 NiO 4 , merely due to the fact that the system appears with robust charge stripe ordering for this doping, making it a suitable system to address various functions of the TMO perovskites.…”
Section: Iintroductionmentioning
confidence: 99%
“…[18][19][20][21][22] On the other hand, a tetragonal symmetry (I4/mmm) was suggested for La 2¹x Sr x NiO 4+¤ at higher temperatures. [20][21][22] The authors found that the diffraction patterns for all composition can be indexed by the tetragonal symmetry, I4/mmm, and no obvious advantages of orthorhombic symmetry as earlier work were suggested. 23,24 Therefore, the authors calculate the lattice parameters assuming the tetragonal symmetry by using the software TOPAS (Bruker AXS).…”
Section: Thermochemical Deformation Of La 2 Nio 4 -Based Oxidesmentioning
confidence: 99%
“…However, only a limited number of materials have shown appropriate diffraction peaks. The clearest cases are La 2−x Sr x NiO 4 [22] and the 1/8th doped cuprates [8,9]. Another possible candidate for stripe phases identified through diffraction is superoxygenated and phase separated La 2−x Sr x CuO 4+y [16].…”
Section: Pacs Numbersmentioning
confidence: 99%